Laser Surface Treatment for Targeted Strengthening of Metallic Multilayer Thin Films - Stossel, Melicent (My University, 2025)
In this dissertation, pulsed laser surface treatment is applied to two multilayer thin film material systems, Ti/Ni and Cu/Al, to locally strengthen the surface layers of a multilayer film while preserving the original structure and properties of the base layers. Picosecond laser surface treatment was applied to Ti/Ni to investigate the effect of laser pulse energy, individual layer thickness, and total film thickness on the surface strengthening. Intermetallic phase precipitation was shown to be a dominant mechanism for laser-induced strengthening of the Ti/Ni multilayer. Therefore, Cu/Al, a material with a plethora of potential intermetallic phases, was treated with nano- and picosecond pulse lasers to generate intermetallic phases with the goal of confined surface strengthening. The laser surface treatment method was then applied as an array to optimize the laser treatment parameters for scaling to industrial applications.Picosecond pulsed laser treatment of Ti/Ni showed that for increasing laser pulse energy, the multilayer cross-section initially consists of a clear multilayer structure, followed by the onset of an intermixed layer at the film surface that grows in thickness as energy increases until the film is fully intermixed. Intermixing was not sufficient to cause surface strengthening, instead there was an increase in hardness after intermetallic phases were generated at higher pulse energy. The effect of individual layer thickness was compared between 20 nm and 50 nm layers, and the results showed that the formation of an intermixed layer and the onset of intermetallic phase precipitation required less energy for larger layers. Incorporating the effect of a 500 nm and 1 µm total film thickness shows more energy is required to generate the intermixed layer and reach the critical energy to form intermetallic phases for thicker Ti/Ni films. Initial testing of the Cu/Al multilayer system revealed a reflectivity of over 90% when treated with light at 1064 nm, necessitating the addition of a 25 nm Ti capping layer to improve absorption of the incident energy. Nanosecond and picosecond pulsed laser treatments were applied to the Cu/Al + Ti multilayer films to generate intermetallic phases and measure the corresponding increase in hardness. Surface treatment with the nanosecond laser resulted in a smooth, microcracked surface with no intermixed layer but a dramatic increase in hardness to a maximum of over 10 GPa for nanoindentation at shallow contact depth that decreases to the as-deposited hardness of around 4 GPa with increasing contact depth. Picosecond laser treatment results in the formation of a highly textured surface and an intermixed layer with clear intermetallic phase generation, however the resulting strengthening is generally limited to 5-7 GPa over a range of shallow contact depths. Picosecond laser treatment was applied in a hexagonal array pattern to extend the treatment from a single location test to an area treatment. Arrays were created with 0% shot overlap as well as 50% shot overlap in x and y directions. Both single-pulse arrays and multiple pulse arrays were generated, with an emphasis on developing single-pulse arrays that show clear intermetallic phase generation and a corresponding increase in hardness to avoid complications associated with multi-pulse testing such as thermal accumulation.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Copper Aluminum; Intermetallic; Laser surface treatment; Multilayer thin film; Surface strengthening; Titanium Nickel; Mechanical engineering; Materials Science; Mechanical engineering